Interseções: cartografias possíveis de uma mulher artista professora: conversas decoloniais - Gabriela Alvarenga Cardoso Silva (2022)
In this research I investigate the teaching and learning processes in art. Also, I analyse my artistic creation and production from a decolonial feminist perspective. I build this text using Virginia Kastrupp's methodology of clues, crossing my experience as a woman-teacher-artist. From the experience with students, I research the absence of women artists in teaching and learning in art and possibilities of resistance to this Eurocentric historical construction. To carry out this analysis, I work on the concept of intersectionality by Lugones, the history of the witch hunt elaborated by Silvia Federici, the concept of chi'xi and the feminism of Silvia Rivera Cusicanqui. Above all, I dialogue in the text and in the experiences in the classroom with three Brazilian artists, Castiel Vitorino Brasileiro, Rosana Paulino and Sallisa Rosa. Through Catherine Walsh's eyes, I also focus on the understanding of what a decolonial feminism would be and on how research itself was transformative in my everyday being as a woman. Throughout the research I also came across with other clues and interventions by artists, poets, curators and theorists who spoke poetically with my encounters with words, images and the classroom. This text, then, does not shy away from a poetic writing, which starts from my experiences and narratives for an understanding of knowledge structures in art forged by a white elite of cisgender men. In addition to navigating through the structures of this system, I seek, throughout the text, everyday strategies to break them and give new meaning to them.